Srebrica Knežević: Аcademic and Pedagogical Framework in Ethnology and Anthropology - Mitrović (Serbia), Katarina M. (Bulletin of the Institute of Ethnography SASA, 2018)
This paper reviews the life and work of Srebrica Knežević (1930-2012) in order to present her career, achievements and fields of study that she contributed to. Special attention will be paid to the importance of her role in pioneer research of folk medicine, nutrition and world ethnology, as well as comprehension of the significance of interdisciplinary approach in Serbian ethnology. Also, this paper will depict Srebrica Knežević as a researcher loyal to her ethnographic field, therefore indicating the compromises she had to make for her very frequent trips and researches. Finally, I will speak of Srebrica Knežević as a lecturer and a professor who adjusted her impressions for the classroom setting and her students, during four decades of work at the Department of Ethnology and Anthropology of the Faculty of Philosophy in Belgrade. As a gifted lecturer who implemented innovations in the classroom, she is remembered as a creative, passionate and dedicated professor, who brought distant topics and ethnographic fields to life. The life and work of Srebrica Knežević are presented and analyzed based on the relevant literature and conversations with her colleagues, students, friends and family. Key words: Srebrica Knežević, ethnology, folk medicine, nutrition, world ethnology